Crisis Communication Strategy For Bpjs Outpatient Patients At Muhammadiyah Palembang - Chandra Saputra (CV. Doki Course and Training, 2025)
This article describes the results of community service activities that discuss communication strategies in crisis management for BPJS outpatients at the Muhammadiyah Hospital in Palembang. Along with increasing concerns about patient dissatisfaction due to long waiting times and inadequate communication, this activity aims to examine the role of health communication strategies in mitigating the crisis. The methods used include interviews, observations, and document analysis to explore the effectiveness of communication between hospital staff and patients. The results of this service identified significant improvements in communication response times and patient satisfaction, while highlighting the importance of transparency and empathy in crisis management. This study contributes to the understanding of the practical application of communication strategies in health services, with implications for improving patient experiences in the health care system in Indonesia.